Properties and Biocompatibility of Chitosan and Silk Fibroin Blend Films for Application in Skin Tissue Engineering. (22nd May 2012) - Luangbudnark, Witoo; Viyoch, Jarupa; Laupattarakasem, Wiroon; Surakunprapha, Palakorn; Laupattarakasem, Pisamai
Abstract : Chitosan/silk fibroin (CS/SF) blend films were prepared and evaluated for feasibility of using the films as biomaterial for skin tissue engineering application. Fourier transform infrared spectroscopy and differential scanning calorimetry analysis indicated chemical interaction between chitosan and fibroin. Chitosan enhanced β -sheet conformation of fibroin and resulted in shifting of thermal degradation of the films. Flexibility, swelling index, and enzyme degradation were also increased by the chitosan content of the blend films. Biocompatibility of the blend films was determined by cultivation with fibroblast cells. All films showed no cytotoxicity by XTT assay. Fibroblast cells spread on CS/SF films via dendritic extensions, and cell-cell interactions were noted. Cell proliferation on CS/SF films was also demonstrated, and their phenotype was examined by the expression of collagen type I gene. These results showed possibility of using the CS/SF films as a supporting material for further study on skin tissue engineering.